The coagulant action of dispholidus typus (boomslang) venom - Atkinson, P. M. (My University, 1980)
Dispholidus typus also known as the boomslang is an arboreal back fanged member of the Colubridae and is indigenous to South Africa. Death in human victims is due to disseminated intra-vascular coagulation. Few studies had previously been undertaken to determine the venom's mechanism of action.
A Thesis submitted to the Faculty of Medicine, University of the Witwatersrand, for the Degree of Doctor of Philosophy in Medicine